Distinct roles for the Charcot–Marie–Tooth disease-causing endosomal regulators Mtmr5 and Mtmr13 in axon radial sorting and Schwann cell myelination. Issue 8 (27th October 2021) - Mammel, Anna E; Delgado, Katherine C; Chin, Andrea L; Condon, Alec F; Hill, Jo Q; Aicher, Sue A; Wang, Yingming; Fedorov, Lev M; Robinson, Fred L
Abstract: The form of Charcot–Marie–Tooth type 4B (CMT4B) disease caused by mutations in myotubularin-related 5 ( MTMR5 ; also called SET binding factor 1, SBF1 ) shows a spectrum of axonal and demyelinating nerve phenotypes. This contrasts with the CMT4B subtypes caused by MTMR2 or MTMR13 ( SBF2 ) mutations, which are characterized by myelin outfoldings and classic demyelination. Thus, it is unclear whether MTMR5 plays an analogous or distinct role from that of its homolog, MTMR13, in the peripheral nervous system (PNS). MTMR5 and MTMR13 are pseudophosphatases predicted to regulate endosomal trafficking by activating Rab GTPases and binding to the phosphoinositide 3-phosphatase MTMR2. In the mouse PNS, Mtmr2 was required to maintain wild-type levels of Mtmr5 and Mtmr13, suggesting that these factors function in discrete protein complexes. Genetic elimination of both Mtmr5 and Mtmr13 in mice led to perinatal lethality, indicating that the two proteins have partially redundant functions during embryogenesis. Loss of Mtmr5 in mice did not cause CMT4B-like myelin outfoldings. However, adult Mtmr5 −/− mouse nerves contained fewer myelinated axons than control nerves, likely as a result of axon radial sorting defects. Consistently, Mtmr5 levels were highest during axon radial sorting and fell sharply after postnatal day seven. Our findings suggest that Mtmr5 and Mtmr13 ensure proper axon radial sorting and Schwann cell myelination, respectively, perhaps through their direct interactions with Mtmr2. This study enhances our understanding of the non-redundant roles of the endosomal regulators MTMR5 and MTMR13 during normal peripheral nerve development and disease.